Clinical diagnosis by laboratory methods : a working manual of clinical pathology - Todd, James Campbell; Sanford, Arthur Hawley (W. B. Saunders company, 1927)
The manual focuses on various methods of clinical laboratory diagnosis. Intended for professional public.
Keywords: klinické laboratorní techniky; Clinical Laboratory Techniques; diagnostika